Dimensione, rilievo e rilevanza del Terzo Settore. Qualche riflessione a margine della sentenza della Corte costituzionale n. 131 del 2020 (Società e diritti, 2023)
The decision of the Constitutional Court n. 131 of 2020 clarified the essential characteristics of the c.d. “constitutional statute” of the Third Sector, after the innovations introduced by the Third Sector Code. In particular, the ruling focuses on the connection between the principle of social solidarity and the principle of “horizontal subsidiarity”. The author takes his cue from the holding and reconstructs the debate on the subject in a triple perspective of investigation. Finally, the paper highlights some problematic profiles left unresolved by the sentence.
Keywords: Constitution – person – social formations – solidarity – subsidiarity – Third Sector.